Digital innovations and agricultural transformation in Africa: Lessons from Kenya - Tabe-Ojong, Martin Paul Jr.; Abate, Gashaw T.; Abay, Kibrom A.; Spielman, David J. (International Food Policy Research Institute, 2023)
Digital innovation is a key feature in the global and national discourse on food systems transformation. Efforts to better integrate food systems—defined here as the constellation of actors and their activities originating from agriculture, livestock, forestry, or fisheries, as well as the broader economic, societal, and natural environments in which they operate, including the production, aggregation, processing, distribution, consumption, and disposal of food products (Dwivedi et al. 2017; FAO 2018; Njuki et al. 2021)—will depend partly on how digital technologies can be used to bolster engagement, coordination, and innovation among a wider and more inclusive set of actors, including marginalized and vulnerable groups (Benfica et al. 2021).